PENGARUH LOKASI, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI NIAT BELI KONSUMEN SEBAGAI VARIABEL MEDIASI PADA CAFÉ KEDAI GARASI INSPIRASI DI LANGOWAN - Nikita Debora Mawar Rau; Imelda W. J. Ogi; Rudy S. Wenas (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
ABSTRACT This study aims to analyze the influence of location, price, and product quality on customer satisfaction through purchase intention as a mediating variable at Café Kedai Garasi Inspirasi in Langowan. This study used a quantitative method with a sample of 100 respondents. Data analysis was conducted using SEM-PLS with SmartPLS software. The results showed that location and product quality did not significantly affect purchase intention, while price had a positive and significant effect on purchase intention. Purchase intention had a positive and significant effect on customer satisfaction. In mediation testing, only price significantly affected customer satisfaction through purchase intention. The conclusion of this study indicates that price is the most dominant factor in increasing purchase intention and customer satisfaction at Café Kedai Garasi Inspirasi in Langowan. Keywords: Location, Price, Product Quality, Purchase Intention, Customer Satisfaction, SEM-PLS